The Science of Misremembering: Causes, Consequences, and Correction of False Memories - Arysha Shahid; Sara Akbar Awan; Hajra Waheed Kayani; Ushna Seher; Mamoona Tariq; Mehreen Faiza (Research Journal of Psychology, 2025)
False memories—distorted or entirely fabricated recollections of past events—are a significant concern in cognitive and applied psychology. This quantitative study examines the psychological causes, consequences, and possible correction strategies for false memories in adult individuals. A sample of 300 participants was surveyed using a standardized instrument designed to assess factors such as suggestibility, cognitive bias, emotional influence, and exposure to misinformation. The data were analyzed using descriptive statistics, Pearson correlation, and multiple regression techniques. Results indicate a strong positive correlation between suggestibility and false memory formation, while emotional intensity and repeated exposure to misleading information were also significant predictors. Furthermore, corrective interventions like source monitoring training and metacognitive awareness were found to reduce the persistence of false memories. These findings contribute to a deeper understanding of memory distortions in psychological functioning and have implications for forensic psychology, educational practices, and therapeutic interventions.